Analisis Implementasi Metode Jigsaw dalam Peningkatan Motivasi Belajar Siswa pada Mata Pelajaran Fikih Kelas VIII di MTs The Noor Pacet-Mojokerto - Aniatus Sholehah; Fina Surya Anggraini; Muhammad Husnur Rofiq (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2022)
Learning activities involve several components for the success of teaching and learning and one of them is by applying effective learning methods which will provide a thorough understanding to students. The research focuses on: (1) How to Implement the Jigsaw Method in Increasing Learning Motivation in Fiqh Lessons Subjects Class VIII, and (2) How to Evaluate the Jigsaw Method in Improving Learning Motivation in Class VIII Fiqh Lessons. The findings in this study is the implementation of the Jigsaw Method in Increasing Students' Learning Motivation in Fiqh Lessons Subjects for Class VIII, the stages are: (a) Giving introduction material, (b) Formation of groups origin, (c) formation of expert groups, (d) Giving different materials/discussion of sub-materials, (e) presentation) Research findings on increasing participants’ learning motivation VIII grade students at Madrasah tsanawiyah The Noor, namely : (a) Able to grow and improve students’ learning enthusiasm, (b) Able to cultivate an unyielding or tenacious spirit, and responsibility, (c) Improve learning effectiveness, and (d) Able to improve student’s learning outcomes.